The Language Of Chemistry Or Chemical Equations
This book provides a sufficient number of equations to the students for practice. In this small book, a large number of equations are written in words, and the student is required to translate them into the Language of Chemistry. The student has to write correct formulae and then balance the equations independently. Just in a week or two, the student learns the method of writing correct balanced equations. Special Features New nomenclature is given. \Test your Understanding\ at the end of each chapter. At the end of the book \Test yourself on these typical questions\ to test your knowledge before the examination. Now the book is in new attractive multicolour format.